Case Report: Rapid renal response to venetoclax monotherapy in a CLL patient with secondary membranous glomerulonephritis - Lovato, Ester; Gangemi, Concetta; Krampera, Mauro; Visco, Carlo; Ferrarini, Isacco (Frontiers in Oncology, 2023)
Membranous glomerulonephritis (MGN) is a rare extra-hematological autoimmune complication of chronic lymphocytic leukemia (CLL), clinically characterized by nephrotic-range proteinuria and, less frequently, renal failure. Because of the rarity of this condition, there is no standardized treatment. Chlorambucil and fludarabine-based regimens, possibly combined with rituximab, have been historically the most frequent therapeutic approaches, with renal response obtained in about two-third of the patients. However, responses are often transient and partial. Here we describe the first patient with rituximab-refractory, CLL-related MGN successfully treated with the Bcl-2 antagonist venetoclax. Nephrotic syndrome resolved as soon as three months after venetoclax initiation, with no unexpected toxicities. At the last follow-up, 17 months after venetoclax start, renal response persists, with proteinuria below 0.5 g/24 hours. This case suggests that targeted agents, particularly Bcl-2 antagonists, might be suitable options for patients with renal autoimmune disorders arising in the context of CLL.